CTCF is dispensable for immune cell transdifferentiation but facilitates an acute inflammatory response - Stik, Grégoire; Vidal, Enrique; Barrero, Mercedes; Cuartero, Sergi; Vila-Casadesús, Maria; Mendieta-Esteban, Julen; Tian, Tian V.; Choi, Jinmi; Berenguer, Clara; Abad, Amaya; Borsari, Beatrice; le Dily, François; et al. (Nature genetics, 2020)
Three-dimensional organization of the genome is important for transcriptional regulation 1 – 7 . In mammals, CTCF and the cohesin complex create submegabase structures with elevated internal chromatin contact frequencies, called topologically associating domains (TADs) 8 – 12 . Although TADs can contribute to transcriptional regulation, ablation of TAD organization by disrupting CTCF or the cohesin complex causes modest gene expression changes 13 – 16 . In contrast, CTCF is required for cell cycle regulation 17 , embryonic development and formation of various adult cell types 18 . To uncouple the role of CTCF in cell-state transitions and cell proliferation, we studied the effect of CTCF depletion during the conversion of human leukemic B cells into macrophages with minimal cell division. CTCF depletion disrupts TAD organization but not cell transdifferentiation. In contrast, CTCF depletion in induced macrophages impairs the full-blown upregulation of inflammatory genes after exposure to endotoxin. Our results demonstrate that CTCF-dependent genome topology is not strictly required for a functional cell-fate conversion but facilitates a rapid and efficient response to an external stimulus. CTCF is dispensable for transdifferentiation of B cells into induced macrophages despite widespread loss of topologically associating domains. CTCF depletion impairs upregulation of inflammatory genes after endotoxin exposure by destabilizing promoter–enhancer interactions.